Trustworthiness in Mobile Cyber Physical Systems - Kang, Kyungtae; Son, Junggab; Suh, Hyo-Joong (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Computing and communication capabilities are increasingly embedded in diverse objects and structures in the physical environment. They will link the 'cyberworld' of computing and communications with the physical world. These applications are called cyber physical systems (CPS). Obviously, the increased involvement of real-world entities leads to a greater demand for trustworthy systems. Hence, we use "system trustworthiness" here, which can guarantee continuous service in the presence of internal errors or external attacks. Mobile CPS (MCPS) is a prominent subcategory of CPS in which the physical component has no permanent location. Mobile Internet devices already provide ubiquitous platforms for building novel MCPS applications. The objective of this Special Issue is to contribute to research in modern/future trustworthy MCPS, including design, modeling, simulation, dependability, and so on. It is imperative to address the issues which are critical to their mobility, report significant advances in the underlying science, and discuss the challenges of development and implementation in various applications of MCPS.